Zakres funkcjonowania systemu HACCP na przykładzie Zakładów Jajczarskich "Ovopol" sp. z o.o. w Nowej Soli - Śnihur, Janusz (Range of Functioning of HACCP System on the Example of "Ovopol" Ltd. Nowa Sol, 2005)
Integration process, new markets and expectations of purchasers force fitting the process of fabricating for norms assuring the highest quality. The article presents a process and range of application of system of HACCP norm in food industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 348-354